Literacy development in Kalimantan, Indonesia - Hamudy, Moh Ilham A; Rifki, M. Saidi (Jurnal Kajian Informasi dan Perpustakaan, 2024)
Literacy development in Kalimantan has its ups and downs. Some regions in Kalimantan have experienced increases and decreases. The East Kalimantan ranks in the top 10 provinces with the highest National Reading Interest Level (TGM), and only South Kalimantan achieved the highest Community Literacy Development Index (IPLM). Some other regions experienced a decrease. The aims this research to determine literacy development in Kalimantan, Indonesia with analysis factors hinder it, and what factors contribute to its success. Method research used a descriptive qualitative. The study covered the period 2019 to 2021. The results revealed that several contributing factors to the low literacy development, including limited library human resources, ineffective leadership, bureaucratic politicization, poor planning, and dualism in literacy budgeting. However, the study also identified success factors, such as effective communication between leaders and staff and support from various stakeholders. The research conclusion states that literacy development in Kalimantan of low, identify inhibiting factors, find success factors, and provide recommendations for improvement. In conclusion, the low level of literacy development in Kalimantan is due to several inhibiting factors; however, there are also success factors that can guide improvement. The importance of effective communication and collaboration between librarians and the government to enhance competency and literacy development.